Metaldehyde: a brief on biodegradation and detection methods / Azlina Mat Saad - Mat Saad, Azlina; Ismail, Syamimi Wahida; Dahalan, Farrah Aini; Abu Hassan Asari, Fadli Fizari (2018)
Metaldehyde has been used to eradicate plant pests such as golden apple snails and slugs. This toxic pesticide has adverse effects on the environment including human health and animals. The biodegradation process naturally reduces the toxicity of this harmful pesticide, but in a long term. Many studies have been conducted in analysing the biodegradation process in water and soil. In addition, various methods have been proposed in detecting this pesticide, especially in the aquatic environment. Both biodegradation and detection are essential fields in ensuring the sustainability of our environment. This paper gives a brief idea on both concepts, and works as a platform for young researchers in the environmental pollution.